The Acts of the Apostles as a Portrayal of the Synodal Church? - Mielcarek, Krzysztof (Verbum vitae, 2025)
This article explores the concept of synodality in the Acts of the Apostles. Although the term σύνοδος is absent from the New Testament, potentially leading to premature negative assumptions, an etymological analysis of its components (the preposition σύν and the noun ἡ ὁδός) yields more positive insights. Drawing on synodal documents and selected passages from Luke’s second volume, the study establishes certain connections between the modern notion of synodality and the practices of the early Church, delineating essential criteria for the attitudes of members within today’s synodal Church.